Betaine supplementation improves 60 km cycling time trial performance and one-carbon metabolism in cyclists during recovery - Nieman, D. C.; Sakaguchi, C. A.; Williams, J. C.; Lawson, J.; Lambirth, K. C. (Nutrients, 2025)
Background/Objectives: This study examined the effects of 2 weeks of betaine versus placebo supplementation (3 g/d) on 60 km cycling performance, gut permeability, and shifts in plasma metabolites.